Modeling strategies in teaching critical thinking in Islamic education - Nursafra Mohd Zhaffar; Norwati Abu Bakar; Nurul Asiah Fasehah Muhamad (Penerbit Universiti Kebangsaan Malaysia, 2025)
Critical teachers are needed to develop critical students. A teacher's appearance in terms of actions, speech, and critical thinking sets a powerful example that students might emulate. However, research indicates that modeling becomes less effective if the actions to be emulated do not come with clear instructions meant for the intended audience. Therefore, this study aims to explore modeling strategies in the teaching of Islamic Education (IE) that incorporate critical thinking by excellent Islamic Education teachers. The purpose of this modeling carried out by teachers is to ensure that the skills, attitudes, and values of critical thinking can be emulated by students. This study is a qualitative case study involving a group of six excellent Islamic Education teachers. Data were collected over a period of 12 months using interviews, classroom observations, and document analysis. The findings reveal two main themes in the teachers' modeling strategies: modeling through teaching techniques and modeling through the teachers' overall behavior. The study found that teachers implemented modeling strategies by demonstrating the boundaries of thinking in IE teaching, guiding students to develop a thinking framework based on Islamic principles. This research suggests that effective modeling in fostering critical thinking requires teachers to integrate both explicit and implicit applications of thinking in their teaching practices routinely. This continuous process helps students become aware of their thinking skills and apply them within the framework of a Muslim lifestyle. A conceptual framework for the modeling of critical thinking in Islamic education has been developed by this study.